Photochromic material as well as preparation method and application thereof
By adding crosslinking agent to the photochromic material to form a stable crosslinking network structure, and forming nanoparticles through spray drying, the problem of degradation in the performance of existing photochromic materials is solved, and the service life and oxygen permeability of the discolorable contact lenses are improved.
Patent Information
- Application Number
- CN202411880509.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
The performance of existing photochromic materials deteriorates during long-term and frequent discoloration, resulting in a short service life of discolorable contact lenses.
By adding crosslinking agent and controlling the amount of crosslinking agent, the degree of crosslinking of photochromic materials is adjusted to form a stable crosslinking network structure, enhancing the photochromic effect and durability of the material, and forming nanoparticles through spray drying, improving the specific surface area and dispersion of the material.
It improves the durability and color distortion ability of photochromic materials, extends the service life of color-changing contact lenses, and improves oxygen permeability and UV resistance.
Smart Images

Figure BDA0005198130640000071 
Figure BDA0005198130640000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to a photochromic material and a preparation method and application thereof. Background Art
[0002] Color-changing contact lenses are contact lenses that can automatically change color according to external environmental factors (such as light intensity, temperature, etc.). The color-changing principle is mainly based on the characteristics of photochromic materials. When exposed to light of a specific wavelength, the molecular structure of the photochromic material changes, resulting in a color change.
[0003] Currently, photochromic contact lenses containing photochromic materials can automatically adjust the color depth according to the brightness of the ambient light, automatically darken under strong light, reduce glare, and allow the eyes to always receive a comfortable amount of light, improving visual comfort. However, photochromic materials may experience performance degradation during long-term and frequent color changes, such as weakened color change effects and narrowed color change ranges, which will affect the service life of color-changing contact lenses and require more frequent replacement.
[0004] Therefore, there is an urgent need to provide a photochromic material with excellent color-changing performance and durability and a preparation method thereof to increase the service life of color-changing contact lenses. Summary of the invention
[0005] In view of this, the present invention provides a photochromic material and a preparation method and application thereof, so as to solve the problem that the existing photochromic materials have poor color changing performance and durability, resulting in a short service life of color-changing contact lenses.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a method for preparing a photochromic material, comprising the following steps:
[0008] 1) mixing polyvinyl alcohol, glyoxylic acid, a catalyst and water to react and obtain a polymer;
[0009] 2) mixing the polymer obtained in step 1), o-phenanthroline, dibenzoylmethane, EuCl3, a crosslinking agent and a first organic solvent, and reacting them to obtain an intermediate product;
[0010] 3) dissolving the intermediate product in a second organic solvent and spray drying the mixture to obtain a photochromic material.
[0011] Preferably, in step 1), the molar ratio of polyvinyl alcohol to glyoxylic acid is 1:3-8; the mass volume ratio of polyvinyl alcohol to catalyst and water is 120-300 g: 0.12-30 g: 400-1000 mL.
[0012] Preferably, the reaction temperature in step 1) is 50-90° C. and the reaction time is 2-5 h.
[0013] Preferably, the catalyst comprises one or more of acetic acid, sulfuric acid, benzenesulfonic acid and p-toluenesulfonic acid.
[0014] Preferably, in step 2), the molar ratio of the polymer, o-phenanthroline, dibenzoylmethane and EuCl3 is 0.01:2-5:7-9:2-5; the mass volume ratio of the polymer to the cross-linking agent and the first organic solvent is 10g:0.5-3.0g:10-80mL.
[0015] Preferably, the reaction temperature in step 2) is 50-110° C. and the reaction time is 0.1-1 h.
[0016] Preferably, the cross-linking agent includes one or more of diallyl phthalate, trimethylolpropane triacrylate, pentaerythritol triacrylate, ethylene glycol dimethacrylate, ethylene glycol diester diacrylate, diphenylmethane diisocyanate and triallyl diisocyanate; and the first organic solvent includes one or more of methanol, ethanol, acetone and isopropanol.
[0017] Preferably, the mass volume ratio of the intermediate product to the second organic solvent in step 3) is 5-10 g:50-100 mL; the spray drying pressure is 0.1-0.3 MPa, the temperature is 110-180° C., and the time is 1-2 h; the second organic solvent includes one or more of dimethylformamide, tetrahydrofuran and toluene.
[0018] The present invention also provides a photochromic material prepared by the method for preparing the photochromic material.
[0019] The present invention also provides an application of the photochromic material in preparing color-changing contact lenses.
[0020] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention can adjust the crosslinking degree of the photochromic material by adding a crosslinking agent and controlling the amount of the crosslinking agent added, forming a stable crosslinking network structure, so that the photochromic process can be carried out more standardized, which helps to enhance the photochromic effect of the material, improve the ability of the material to withstand multiple photochromic cycles, that is, improve the durability of the material, thereby increasing the service life of the color-changing contact lens, and can also increase the oxygen permeability coefficient of the color-changing contact lens. At the same time, this stable crosslinking network structure can also make the surface of the material more wear-resistant, reducing the degradation of the photochromic performance caused by material shedding or surface wear during the friction process.
[0022] The present invention forms a photochromic material of nanoparticles by spray drying, increases the specific surface area of the photochromic material, and makes it have better dispersibility, thereby ensuring that the photochromic material will not agglomerate during the curing process, and can maintain stable performance during multiple color change cycles, thereby extending the service life of the color-changing contact lens. At the same time, since the photochromic material of the present invention has a high specific surface area, it can more sensitively perceive changes in light intensity and wavelength, thereby changing color faster, greatly improving the color-changing ability and oxygen permeability of the color-changing contact lens.
[0023] The preparation method of the photochromic material of the present invention is simple, has high yield, low cost, and has broad application prospects. At the same time, the color-changing contact lenses prepared from the photochromic material of the present invention have excellent ultraviolet protection and color-changing ability, long service life, good visual effect and no foreign body sensation. DETAILED DESCRIPTION
[0024] The present invention provides a method for preparing a photochromic material, comprising the following steps:
[0025] 1) mixing polyvinyl alcohol, glyoxylic acid, a catalyst and water to react and obtain a polymer;
[0026] 2) mixing the polymer obtained in step 1), o-phenanthroline, dibenzoylmethane, EuCl3, a crosslinking agent and a first organic solvent, and reacting them to obtain an intermediate product;
[0027] 3) dissolving the intermediate product in a second organic solvent and spray drying the mixture to obtain a photochromic material.
[0028] In the present invention, the molar ratio of polyvinyl alcohol to glyoxylic acid in step 1) is 1:3-8, preferably 1:3.5-7.5, more preferably 1:5-6.5, and more preferably 1:6; the mass volume ratio of polyvinyl alcohol to catalyst and water is 120-300 g: 0.12-30 g: 400-1000 mL, preferably 130-280 g: 0.13-28 g: 500-900 mL, more preferably 150-250 g: 0.15-25 g: 600-800 mL, and more preferably 180-200 g: 0.18-20 g: 650-700 mL.
[0029] In the present invention, the reaction temperature in step 1) is 50-90°C, preferably 55-80°C, more preferably 60-75°C, and more preferably 65-70°C; the reaction time is 2-5h, preferably 2.5-4.5h, more preferably 3-4h, and more preferably 3.5h; the reaction conditions are preferably an inert atmosphere, and the inert atmosphere is preferably one of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere, and more preferably a nitrogen atmosphere.
[0030] In the present invention, the catalyst includes one or more of acetic acid, sulfuric acid, benzenesulfonic acid and p-toluenesulfonic acid.
[0031] In the present invention, the average molecular weight of the polyvinyl alcohol is preferably 6,000.
[0032] In the present invention, the molar ratio of the polymer, o-phenanthroline, dibenzoylmethane and EuCl3 in step 2) is 0.01:2-5:7-9:2-5, preferably 0.01:2.5-4.5:7.5-8.5:2.5-3.5, and more preferably 0.01:3:8:3; the mass volume ratio of the polymer to the cross-linking agent and the first organic solvent is 10g:0.5-3.0g:10-80mL, preferably 10g:0.6-2.8g:15-75mL, further preferably 10g:0.8-2.5g:20-70mL, and more preferably 10g:1.0-2.2g:30-65mL.
[0033] In the present invention, the reaction temperature in step 2) is 50-110°C, preferably 60-100°C, more preferably 65-95°C, and more preferably 70-80°C; the reaction time is 0.1-1h, preferably 0.2-0.9h, more preferably 0.3-0.7h, and more preferably 0.5h; the reaction conditions are preferably an inert atmosphere, and the inert atmosphere is preferably one of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere, and more preferably a nitrogen atmosphere.
[0034] In the present invention, the cross-linking agent includes one or more of diallyl phthalate, trimethylolpropane triacrylate, pentaerythritol triacrylate, ethylene glycol dimethacrylate, ethylene glycol diester diacrylate, diphenylmethane diisocyanate and triallyl diisocyanate; the first organic solvent includes one or more of methanol, ethanol, acetone and isopropanol.
[0035] In the present invention, the mass volume ratio of the intermediate product to the second organic solvent in step 3) is 5-10 g:50-100 mL, preferably 6-9 g:60-95 mL, and more preferably 7-8 g:65-80 mL.
[0036] In the present invention, the spray drying pressure in step 3) is 0.1-0.3 MPa, preferably 0.15-0.25 MPa, and more preferably 0.2 MPa; the temperature is 110-180°C, preferably 115-175°C, further preferably 125-170°C, and more preferably 150-160°C; the time is 1-2 h, preferably 1.2-1.8 h, and more preferably 1.5 h.
[0037] In the present invention, the second organic solvent in step 3) comprises one or more of dimethylformamide, tetrahydrofuran and toluene.
[0038] The present invention also provides a photochromic material prepared by the method for preparing the photochromic material.
[0039] The present invention also provides an application of the photochromic material in preparing color-changing contact lenses.
[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0041] Example 1
[0042] 1) polyvinyl alcohol (150 g, 0.025 mol) with an average molecular weight of 6000, glyoxylic acid (11 g, 0.15 mol), 4 g sulfuric acid and 800 mL of water were mixed, and reacted under a nitrogen atmosphere at a temperature of 80° C. for 3.5 h to obtain a polymer;
[0043] 2) After mixing the polymer (6.84 g, 0.001 mol) obtained in step 1), o-phenanthroline (72 g, 0.4 mol), dibenzoylmethane (179.4 g, 0.8 mol) and 50 mL of methanol, EuCl3 (103.2 g, 0.4 mol) and 1.7 g of trimethylolpropane triacrylate were added, and the mixture was reacted under a nitrogen atmosphere at a temperature of 65° C. for 1 h to obtain an intermediate product;
[0044] 3) 30 g of the intermediate product was dissolved in 500 mL of dimethylformamide, and spray-dried at a pressure of 0.15 MPa and a temperature of 175° C. for 1 h to obtain a photochromic material.
[0045] Example 2
[0046] 1) polyvinyl alcohol (180 g, 0.03 mol) with an average molecular weight of 6000, glyoxylic acid (11 g, 0.15 mol), 10 g acetic acid and 500 mL of water were mixed, and reacted under a nitrogen atmosphere at a temperature of 55° C. for 5 h to obtain a polymer;
[0047] 2) After mixing the polymer (13.68 g, 0.002 mol) obtained in step 1), o-phenanthroline (144 g, 0.8 mol), dibenzoylmethane (358.8 g, 1.6 mol) and 90 mL of acetone, EuCl3 (206.4 g, 0.8 mol) and 2.5 g of diallyl phthalate were added, and the mixture was reacted under a nitrogen atmosphere at a temperature of 80° C. for 0.5 h to obtain an intermediate product;
[0048] 3) 50 g of the intermediate product was dissolved in 600 mL of dimethylformamide, and spray-dried at a pressure of 0.2 MPa and a temperature of 155° C. for 1.5 h to obtain a photochromic material.
[0049] Example 3
[0050] The only difference between Example 3 and Example 2 is that the amount of diallyl phthalate added in step 2) is 0.7 g.
[0051] Example 4
[0052] The only difference between Example 4 and Example 2 is that the amount of diallyl phthalate added in step 2) is 4.1 g.
[0053] Example 5
[0054] 1) polyvinyl alcohol (300 g, 0.05 mol) with an average molecular weight of 6000, glyoxylic acid (11 g, 0.15 mol), 20 g of benzenesulfonic acid and 1000 mL of water were mixed, and reacted under a nitrogen atmosphere at a temperature of 90° C. for 2 h to obtain a polymer;
[0055] 2) After mixing the polymer (34.20 g, 0.005 mol) obtained in step 1), o-phenanthroline (360 g, 2.0 mol), dibenzoylmethane (897 g, 4.0 mol) and 200 mL of ethanol, EuCl3 (516 g, 2.0 mol) and 1.7 g of ethylene glycol dimethacrylate were added, and the mixture was reacted under a nitrogen atmosphere at a temperature of 110° C. for 0.2 h to obtain an intermediate product;
[0056] 3) 60 g of the intermediate product was dissolved in 800 mL of dimethylformamide, and spray-dried at a pressure of 0.3 MPa and a temperature of 115° C. for 2 h to obtain a photochromic material.
[0057] Comparative Example 1
[0058] The only difference between Comparative Example 1 and Example 1 is that no cross-linking agent is added in step 2).
[0059] Comparative Example 2
[0060] The difference between Comparative Example 2 and Example 2 is that the amount of diallyl phthalate added in step 2) is 0.3 g.
[0061] Comparative Example 3
[0062] The difference between this comparative example 3 and example 2 is that the amount of diallyl phthalate added in step 2) is 4.5 g.
[0063] Comparative Example 4
[0064] 1) polyvinyl alcohol (300 g, 0.05 mol) with an average molecular weight of 6000, glyoxylic acid (11 g, 0.15 mol), 20 g of benzenesulfonic acid and 1000 mL of water were mixed, and reacted under a nitrogen atmosphere at a temperature of 90° C. for 2 h to obtain a polymer;
[0065] 2) After mixing the polymer (34.20 g, 0.005 mol) obtained in step 1), o-phenanthroline (360 g, 2.0 mol), dibenzoylmethane (897 g, 4.0 mol) and 200 mL of ethanol, add EuCl3 (516 g, 2.0 mol) and 1.7 g of ethylene glycol dimethacrylate, and react in a nitrogen atmosphere at a temperature of 110°C for 0.2 h to obtain a photochromic material.
[0066] The photochromic materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were solidified and then immersed in 70% ethanol aqueous solution, deionized water and physiological saline for 4 hours respectively to obtain color-changing contact lenses. The prepared color-changing contact lenses were tested as follows.
[0067] Experimental Example 1
[0068] The oxygen permeability coefficient of the color-changing contact lenses prepared from the photochromic materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was tested. The specific test method was based on GBT 11417.7-2012 "Ophthalmic Optical Contact Lenses Part 7: Physical and Chemical Properties Test Methods". The test results are shown in Table 1.
[0069] Table 1 Oxygen permeability coefficient of photochromic contact lenses prepared from photochromic materials
[0070] sample Oxygen permeability Example 1 120 Example 2 120 Example 3 115 Example 4 121 Example 5 120 Comparative Example 1 112 Comparative Example 2 110 Comparative Example 3 90 Comparative Example 4 112
[0071] As shown in Table 1, the oxygen permeability coefficient of the color-changing contact lens prepared by the photochromic material prepared by the preparation method of the present invention is better, that is, the ability of oxygen to pass through the lens is stronger, which is more beneficial to the health of the eyes and meets the requirements of the color-changing contact lens for oxygen permeability. In addition, from the oxygen permeability coefficient results of the color-changing contact lens prepared by the photochromic material in Example 2 and Comparative Examples 2 to 3, it can be seen that too much or too little cross-linking agent will significantly affect the oxygen permeability coefficient of the color-changing contact lens, especially too much cross-linking agent will greatly reduce the oxygen permeability coefficient of the color-changing contact lens, because too much cross-linking agent will form a denser cross-linking network, which hinders the diffusion path of oxygen in the material.
[0072] Experimental Example 2
[0073] The light response time and fading time of the color-changing contact lenses prepared from the photochromic materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested using a stopwatch. The results are shown in Table 2.
[0074] Table 2 Response time and half-fading time of photochromic contact lenses prepared from photochromic materials to ultraviolet light
[0075]
[0076]
[0077] As shown in Table 2, the response time and fading time of the photochromic contact lens prepared by the photochromic material prepared by the preparation method of the present invention to ultraviolet light are within the acceptable range of the human eye, and can effectively block ultraviolet rays and reduce the damage of ultraviolet rays to the eyes. This shows that the photochromic material prepared by the present invention has good photosensitivity and reversibility, can quickly undergo a color change reaction under the excitation of ultraviolet light, and quickly recover to the initial state after the ultraviolet light disappears, indicating that the molecular structure and performance of the color-changing material are relatively stable, and can withstand repeated photochemical reactions, thereby extending the service life of the color-changing contact lens.
[0078] Experimental Example 3
[0079] The color-changing contact lenses prepared from the photochromic materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to an aging test. The specific method was as follows: the color-changing contact lenses were irradiated with adjustable ultraviolet rays simulating sunlight, and the temperature of the aging test was set to 35° C., the humidity was set to 50%, the irradiation time was set to 4 hours each time, and the irradiation was performed twice a day. After 4 weeks, the color-changing contact lenses after aging treatment were subjected to performance testing. The results are shown in Table 3.
[0080] Table 3 Performance results of photochromic contact lenses prepared from photochromic materials after aging treatment
[0081] sample Oxygen permeability Response time to UV light, s Half fade time, s Example 1 110 3.55 7.02 Example 2 110 3.55 6.92 Example 3 105 3.58 6.83 Example 4 112 3.56 7.40 Example 5 111 3.55 6.95 Comparative Example 1 99 4.25 6.13 Comparative Example 2 95 3.98 6.25 Comparative Example 3 79 4.09 6.38 Comparative Example 4 100 3.96 6.20
[0082] As shown in Table 3, after the color-changing contact lens prepared by the photochromic material prepared by the preparation method of the present invention is aged, the color-changing contact lens still has a high oxygen permeability coefficient, and can still quickly undergo a color change reaction under the excitation of ultraviolet light, and can quickly return to the initial state after the ultraviolet light disappears, which shows that the photochromic material prepared by the preparation method of the present invention has the ability to withstand multiple photochromic cycles, has excellent durability, and can greatly improve the service life of the color-changing contact lens. At the same time, compared with Comparative Examples 1 to 4, the color-changing contact lens prepared by the photochromic material prepared in Examples 1 to 5 has a longer half-fading time, which shows that the photochromic material of the present invention has good stability. During the use of the color-changing contact lens, the performance of the photochromic material remains relatively stable, and the material structure will not be damaged or the function will not be lost due to repeated color change and fading in a short period of time, thereby extending the service life of the color-changing contact lens.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a photochromic material, characterized in that: The steps include: 1) mixing polyvinyl alcohol, glyoxylic acid, a catalyst and water to react and obtain a polymer; 2) mixing the polymer obtained in step 1), o-phenanthroline, dibenzoylmethane, EuCl3, a crosslinking agent and a first organic solvent, and reacting them to obtain an intermediate product; 3) dissolving the intermediate product in a second organic solvent and spray drying the mixture to obtain a photochromic material.
2. The method for preparing a photochromic material according to claim 1, characterized in that: The molar ratio of polyvinyl alcohol to glyoxylic acid in step 1) is 1:3-8; The mass volume ratio of the polyvinyl alcohol to the catalyst and water is 120-300 g: 0.12-30 g: 400-1000 mL.
3. The method for preparing a photochromic material according to claim 2, characterized in that: The reaction temperature in step 1) is 50-90°C and the reaction time is 2-5h.
4. The method for preparing a photochromic material according to any one of claims 1 to 3, characterized in that: The catalyst includes one or more of acetic acid, sulfuric acid, benzenesulfonic acid and p-toluenesulfonic acid.
5. The method for preparing a photochromic material according to claim 4, characterized in that: The molar ratio of the polymer, o-phenanthroline, dibenzoylmethane and EuCl3 in step 2) is 0.01:2-5:7-9:2-5; The mass volume ratio of the polymer to the cross-linking agent and the first organic solvent is 10 g: 0.5-3.0 g: 10-80 mL.
6. The method for preparing a photochromic material according to claim 5, characterized in that: The reaction temperature in step 2) is 50-110° C. and the reaction time is 0.1-1 h.
7. The method for preparing a photochromic material according to claim 6, characterized in that: The crosslinking agent includes one or more of diallyl phthalate, trimethylolpropane triacrylate, pentaerythritol triacrylate, ethylene glycol dimethacrylate, ethylene glycol diester diacrylate, diphenylmethane diisocyanate and triallyl diisocyanate; The first organic solvent includes one or more of methanol, ethanol, acetone and isopropanol.
8. The method for preparing a photochromic material according to claim 7, characterized in that: The mass volume ratio of the intermediate product to the second organic solvent in step 3) is 5-10 g: 50-100 mL; The spray drying pressure is 0.1-0.3 MPa, the temperature is 110-180°C, and the time is 1-2 hours; The second organic solvent includes one or more of dimethylformamide, tetrahydrofuran and toluene.
9. The photochromic material prepared by the method for preparing a photochromic material according to any one of claims 1 to 8.
10. Use of the photochromic material according to claim 9 in the preparation of color-changing contact lenses.